The Influence of Servant Leadership, Knowledge Management and Strategic Management on Employee Engagement and Management Performance - Ari Sulistyowati; Milda Handayani; Zoel Hutabarat (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The purpose of this study is to see the effect of servant leadership, knowledge management and strategic management on management involvement and performance in start-up companies in Jakarta. The method used in this study is descriptive quantitative. The sample in this study was 105 employees. The sampling technique used was a census. The data used in this study were primary and secondary data. The analysis tools used in this study included SmartPLS. The tests carried out in this study included Validity Test, Reliability Test, Inner Model Test, Outer Model Test, and Hypothesis Test. The results of research conducted at startup companies in Jakarta include: 1) Servant leadership has a positive and significant effect on employee engagement; 2) Knowledge management has a positive and significant effect on employee engagement; 3) Strategic management has no positive and insignificant effect on employee engagement; 4) Servant leadership has a positive and significant effect on management performance; 5) Knowledge management has a positive and significant effect on management performance; and 6) Strategic management has no positive and insignificant effect on management performance. This study is limited to management involvement and performance. The focus on startup companies may limit the generalization of these findings. In addition, although this study uses a questionnaire created by the researcher to ensure its relevance, the data used may be subject to bias, such as social desirability or limited disclosure of unfavorable opinions. This study contributes to the understanding of management performance and employee engagement in startup companies in Jakarta, with a focus on the factors of servant leadership, knowledge management, and strategic management. This research adds new insights related to other factors that influence management involvement and performance, especially in startup companies. So that, later it can be used as reference material in further literature.